"Internal tide pools" prolong kelp forest hypoxic events. (6th October 2017) - Leary, Paul R.; Woodson, C. Brock; Squibb, Michael E.; Denny, Mark W.; Monismith, Stephen G.; Micheli, Fiorenza
Abstract: This study uses field observations within a single kelp bed in southern Monterey Bay, California, to evaluate the retention of cold, hypoxic water within depressions in the rocky reef following relaxation of internal wave events. Just as tide pools in the rocky intertidal zone persist in depressions following the relaxation of surface waves and tides, "internal tide pools" persist in depressions in the subtidal reef following the relaxation of internal waves. When internal waves contain low dissolved oxygen (DO) water, the duration of hypoxic events can be extended for organisms within the pooling zone. Additionally, we suggest that internal wave run‐up can cause the early arrival of cold hypoxic water in these same areas, thereby extending hypoxic events further. Together, internal tide pools and wave run‐up extend event durations by 20% on average. However, some events are extended up to 160% of the regional‐scale event length, which may be more ecologically relevant than the mean extension. When internal waves contain other environmental covariates (e.g., low pH, nutrients), internal tide pools are expected to create a similar time extension and patchy landscape in these quantities. We attribute the slowing of the relaxation of sub‐thermocline water within pooling zones to retention within the reef itself rather than a drag effect of the kelp bed. Following hypoxic internal bores, internal tide pools cause a period of extreme spatial variability in the DO and temperature field which is likely to impact the distribution and behavior of local organisms.